P–775 Obstetric and perinatal outcomes of singleton pregnancies after blastocyst-stage embryo transfer: a systematic review and cumulative meta-analysis. (6th August 2021) - Marconi, N; Allen, C; Bhattacharya, S; Maheshwari, A
Abstract: Study question: Are obstetric/perinatal outcomes different in singleton pregnancies following blastocyst-stage embryo transfer when compared to cleavage-stage embryo transfer and have results changed over time? Summary answer: Pregnancies following blastocyst are consistently associated with higher risk of large for gestational age and lower risk of small for gestational age babies What is known already: Extended embryo culture to blastocyst-stage is widely used to select best embryos in in vitro fertilisation (IVF) cycles to improve pregnancy rates. Transfer of blastocyst-stage embryos is increasing with this being the default strategy in most clinics. As blastocysts are kept in culture until day 5, 6 or 7 after oocyte fertilisation, there are suggestions that longer exposure to culture media may have a negative impact on pregnancy outcomes. More recent primary studies have challenged some of the initial findings. We therefore conducted an updated systematic review and cumulative meta-analysis (CMA) to examine if these results have changed over time. Study design, size, duration: Systematic review of studies published between 1980 and 2020, followed by aggregated meta-analysis and CMA to track the accumulation of evidence over the period of time. Exposed group: singleton pregnancies following blastocyst transfer. Non-exposed group: singleton pregnancies following cleavage-stage transfer. Sub-group analyses were conducted on fresh and frozen-thawed embryo transfers. Perinatal (categories of preterm birth and birth weight) and obstetric outcomes (hypertensive disorders of pregnancy, gestational diabetes, c-section, placental anomalies) were compared between the groups. Participants/materials, setting, methods: Medline, EMBASE, CINHAL, Web of Science, Cochrane Central Register of Clinical Trials and International Clinical Trials Registry Platform databases were searched. Relevant journals were searched for advance access publications. Critical Appraisal Skills Programme (CASP) checklists were used to assess study quality. Two independent reviewers extracted data in 2 × 2 tables. Aggregated and CMA were performed using Comprehensive Meta-Analysis software. Risk ratio (RR) with 95% confidence interval (CI) were calculated. Main results and the role of chance: A total of 33 observational studies were included (n = 574, 756 singleton pregnancies). Pregnancies following blastocyst-stage embryo transfer are associated with a higher risk of preterm birth (PTB) (RR 1.09; 95% CI 1.01–1.17), very preterm birth (VPTB) (RR 1.15; 95% CI 1.07–1.24), large for gestational age (LGA) babies (RR 1.13; 95% CI 1.08–1.19), c-section (RR 1.05; 95% CI 1.02–1.09), and with a lower risk of small for gestational age (SGA) babies (RR 0.86; 95% CI 0.81–0.93) as compared to singleton pregnancies following cleavage-stage embryo transfer. These findings were maintained in both fresh and frozen-thawed sub-groups for LGA and SGA. PTB was not significantly different in both sub-group analyses. The risk of VPTB was higher after blastocyst-stage embryo transfer only in the sub-group analysis of fresh embryo transfers (RR 1.17; 95% CI 1.09–1.27) and that of c-section only in the frozen-thawed sub-group (RR 1.08; 95% CI 1.04–1.12). No other statistically significant differences for the other outcomes were noted. The CMA suggests that for SGA and LGA subsequent studies have increased the precision of the point estimate with no change in the direction or magnitude of the treatment effect since 2014. Limitations, reasons for caution: This analysis was constrained by the intrinsic limitations of observational studies with some of them receiving a CASP score < 10. Adjustment for confounders was not possible and a high degree of clinical and statistical heterogeneity was noted among studies. Wider implications of the findings: Blastocyst is associated with a higher risk of LGA and a lower risk of SGA with a stable body of evidence since 2014. We may need to revisit the default position of extending embryo culture and individualise care, until further high-quality data from individual-patient-data of large registries are available. Trial registration number: Not applicable